The Impact Analysis of Debt to Equity Ratio (DER) and Company Size on Total Assets of Banking Companies on the IDX in 2015 – 2019 - Irma Setyawati (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
This study's objective is to look into the effects of DER, business size, and total assets on Indonesia's banking system. Listed companies on the Indonesian Stock Exchange provide the data needed for this study to be completed. Using a population of 32 banks and a sample size of 9 firms that fit the criteria, this study employed purposive sampling. This study makes use of SPSS 21.0 for Windows for data processing and multivariate linear regression analysis, t and f tests, and other statistical tests. Although partly DER has little influence on overall assets, the size of the company has a big impact. In the study, total assets were found to be affected by both DER and firm size.